PEMBELAJARAN BIOLOGI MELALUI PRAKTIKUM UJI GOLONGAN DARAH BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMA NEGERI 2 TONDANO - Rogahang, Femmy H N; Tengker, Anita C Ch; Pai'pin, Rati Yani (Universitas Negeri Manado, 2020)
The lack of blood type test practicum is carried out this results in student learning outcomes where students are still having difficulties and are wrong in determining blood type and students are not creative in solving problems, because learning is focused on the teacher. This studied aims to improve student learning outcomes through the practice of blood type test based on Problem Based Learning (PBL) for class XI students. This research is a Classroom Action Research (CAR) carried out in two cycles with each cycle consisting of planning, action implementation, observation and reflection. The subjects in this study were students of class XI IPA in the academic year 2019/2020, amounting to 22 students consisting of 8 boys and 14 girls. Data collection techniques through observation, practice, and tests. Based on the results of the study obtained an average student learning outcomes in the first cycle of 66.67 with a percentage of mastery learning classically 31.81% and in the second cycle experienced an increase obtained an average student learning outcomes 88.82 with the percentage of mastery learning classically 90 , 90%. Based on these results it can be concluded that the application of the blood type test practicum with the Problem Based Learning strategy can improve student learning outcomes.